2020
DOI: 10.1111/1365-2435.13671
|View full text |Cite
|
Sign up to set email alerts
|

Ants adjust their tool use strategy in response to foraging risk

Abstract: The ability of animals to make and use tools has greatly fascinated both scientists and the public, because such behaviour was previously thought to be unique to humans. It was not until the 1960s that the first case of animal tool use was reported in chimpanzees (van Lawick-Goodall, 1968). Since then, an increasing number of animals have been reported to be tool users, including some mam

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…A third possibility is that there might be biophysical restrictions on whether an ant can collect a liquid drop between her mandibles. It is likely that small body size makes interactions with liquid droplets more dangerous due to the strong forces of surface tension [40]. We observed that ants make a ‘hasty’ motion at the end of the extraction of the droplet.…”
Section: Discussionmentioning
confidence: 85%
“…A third possibility is that there might be biophysical restrictions on whether an ant can collect a liquid drop between her mandibles. It is likely that small body size makes interactions with liquid droplets more dangerous due to the strong forces of surface tension [40]. We observed that ants make a ‘hasty’ motion at the end of the extraction of the droplet.…”
Section: Discussionmentioning
confidence: 85%
“…By crushing ants in nectar, we exposed bees to all the external and internal chemicals that they might encounter from ants drowned in nectar. Drowning while foraging for liquids is a risk ants (Zhou et al 2020(Zhou et al , 2022 and other insects face (e.g., Robertson 1946;Smith et al 2017;Thien et al 2009). Even in the absence of the physical threat of ants, these chemical stimuli elicited similar responses by bees to when live ants were present.…”
Section: Discussionmentioning
confidence: 99%
“…Drowning is a foraging risk ants face (Zhou et al 2020(Zhou et al , 2022, potentially polluting the nectar quality or taste. To simulate this situation, 50 frozen ants (0.018 g ± 0.000 g) were placed into a tissue homogenizer and crushed into 5mL of 40.6% sucrose solution.…”
Section: Ants In Nectarmentioning
confidence: 99%
“…into liquid food, and then they carry the food-soaked tools back to the nest (e.g., Fellers and Fellers 1976;Banschbach et al 2006). The most typical representatives of this behavior are the members of the genus Aphaenogaster (Fellers and Fellers 1976;Tanaka and Ono 1978;Fowler 1982;McDonald 1984;Agbogba 1985;Cerdá et al 1988;Banschbach et al 2006;Lőrinczi 2014;Maák et al 2017;Lőrinczi et al 2018;Maák et al 2020;Módra et al 2020), but it has also been observed in Messor barbarus (Durán 2011), Messor structor (Módra et al 2017), Novomessor albisetosus (McDonald 1984;Wetterer et al 2002), Pogonomyrmex badius (Morrill 1972), Solenopsis invicta (Barber et al 1989;Qin et al 2019), and Solenopsis richteri (Zhou et al 2020). Contrary to the views of some authors (e.g., Durán 2011), this behavior completely satisfies the criteria of tool use (see Módra et al 2020) according to the currently accepted definition, which is "… the exertion of control over a freely manipulable external object (the tool) with the goal of (1) altering the physical properties of another object, substance, surface or medium (the target, which may be the tool user or another organism) via a dynamic mechanical interaction, or (2) mediating the flow of information between the tool user and the environment or other organisms in the environment" (St. Amant and Horton 2008).…”
Section: Introductionmentioning
confidence: 98%